HLA frequencies in less common arthropathies. Issue 3 (June 1976) - Robitaille, A; Cockburn, C; James, D C; Ansell, B M
Abstract : There was no increased incidence of HLA-B27 in patients suffering from rubella arthropathy, when compared to both the Westminster controls and a group of patients with arthritis secondary to dysentery who nearly all possessed this allele.